Political theory as deconstruction and hegemony theory: Derrida and Laclau and Mouffe - Hansen, Allan Dreyer (Politica, 2026)
The article discusses two versions of post-foundationalism, namely Derrida’s deconstruction and Laclau and Mouffe’s theory of hegemony, as a basis for political theory. Post-foundationalism transforms political theory in two significant ways. Firstly, it problematises the widespread distinction between descriptive empirical political science and normative political theory (is and ought), as all political concepts involve both politics and normativity. This is examined in relation to populism, which serves as a particularly illustrative case. Secondly, it challenges the idea that the task of normative political theory is to provide universal answers to what is morally right. From deconstruction, we gain insight into the simultaneous possibility and impossibility of ideals, such as justice and democracy. Furthermore, hegemony theory demonstrates that these ideals will always be specific interpretations that exclude other possible interpretations. This also applies to discussions about and the application of concepts, meaning that political theory itself emerges as a form of political intervention.